2006
DOI: 10.1162/jocn.2006.18.12.2108
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Brain Activity during Change Blindness and Change Awareness: Performance is Predicted by Neural Events before Change Onset

Abstract: People often remain "blind" to visual changes occurring during a brief interruption of the display. The processing stages responsible for such failure remain unresolved. We used event-related potentials to determine the time course of brain activity during conscious change detection versus change blindness. Participants saw two successive visual displays, each with two faces, and reported whether one of the faces changed between the first and second displays. Relative to blindness, change detection was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
4
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 75 publications
5
65
4
1
Order By: Relevance
“…These results showed that the ERN component, reflecting either conflict detection Yeung et al, 2004) or reinforcement learning (Holroyd & Coles, 2002), may be enhanced by the reduction (i.e., shorter duration) of an earlier non-adjacent anticipatory attentional effect taking place in the precuneus ~190 ms earlier. Attentional shifts during the preparatory baseline time period were already shown to influence the sensory processing of (upcoming/imminent) visual stimuli (see Kondakor et al, 1995;Kastner, Pinsk, De Weerd, Desimone, & Ungerleider, 1999;Super, van der Togt, Spekreijse, & Lamme, 2003;Pourtois et al, 2006). Here I described a similar effect for action monitoring, where the early detection of errors (as reflected by the ERN component) was found to be influenced by the extent to which a putative anticipatory attentional control process, involving posterior parietal brain regions (precuneus), was expressed during the pre-response time period (see also Gevins et al, 1987;Weissman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results showed that the ERN component, reflecting either conflict detection Yeung et al, 2004) or reinforcement learning (Holroyd & Coles, 2002), may be enhanced by the reduction (i.e., shorter duration) of an earlier non-adjacent anticipatory attentional effect taking place in the precuneus ~190 ms earlier. Attentional shifts during the preparatory baseline time period were already shown to influence the sensory processing of (upcoming/imminent) visual stimuli (see Kondakor et al, 1995;Kastner, Pinsk, De Weerd, Desimone, & Ungerleider, 1999;Super, van der Togt, Spekreijse, & Lamme, 2003;Pourtois et al, 2006). Here I described a similar effect for action monitoring, where the early detection of errors (as reflected by the ERN component) was found to be influenced by the extent to which a putative anticipatory attentional control process, involving posterior parietal brain regions (precuneus), was expressed during the pre-response time period (see also Gevins et al, 1987;Weissman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To identify reliable topographic differences between conditions during this pre-response time-period, I used the same procedure for data analysis as already described in previous ERP topographic mapping studies (see Pourtois, Thut, Grave de Peralta, Michel, & Vuilleumier, 2005;Pourtois, Dan, Grandjean, Sander, & Vuilleumier, 2005;Pourtois, De Pretto, Hauert, & Vuilleumier, 2006;see Murray, Brunet, & Michel, 2008;Pourtois, Delplanque, Michel, & Vuilleumier, 2008 for a detailed presentation of the basic principles of this method). Notably, this topographic mapping method was already used to reveal substantial ERP topographic changes across experimental conditions occurring during the pre-stimulus (baseline) time period (see Kondakor, Pascual-Marqui, Michel, & Lehmann, 1995;Pourtois et al, 2006), when the amplitude (strength) of the ERP signal is usually low (close to zero baseline) and therefore where conventional ERP techniques (peak analyses, see Picton et al, 2000) usually fail to disclose reliable differences between experimental conditions (see Pourtois et al, 2008 for a thorough discussion). In this study, I first identified global ERP differences between conditions and distinguished between global differences due to (1) variations in field strength and (2) topography based on the reference-free global field power and the global spatial dissimilarity indices, respectively (Lehmann & Skrandies, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The added value and underlying principles of this data-driven analysis have been described extensively elsewhere (Michel, Seeck, & Landis, 1999;Murray, Brunet, & Michel, 2008;Pourtois, Dan, Grandjean, Sander, & Vuilleumier, 2005;Pourtois et al, 2008;Pourtois, De Pretto, Hauert, & Vuilleumier, 2006;Pourtois, Thut, Grave de Peralta, Michel, & Vuilleumier, 2005). Since the C1 is primarily a location-sensitive early visual ERP, the exact same stimulus would elicit a different topography and strength of the C1 electric field depending on its actual position in the peripheral visual field (Clark et al, 1995).…”
Section: Analyses Of Behavioral Datamentioning
confidence: 99%
“…Indeed, neuroscientific work on these and related topics are well underway (e.g. Beck et al, 2001;Beck et al, 2006;Fernandez-Duque et al, 2003;Huettel et al, 2001;Klucharev et al, 2008;Pourtois et al, 2006;Turatto et al, 2002). And by presenting the scientific study of magic as an attempt to understand how magic tricks work, we risk missing a rather obvious point.…”
Section: A Science Of Neuromagic?mentioning
confidence: 99%